Sosialisasi penanganan pertama pingsan (sinkop) terhadap pengetahuan murid SMPN 1 Kayen Kidul dalam meningkatkan derajat kesehatan siswa sekolah - Didit Damayanti (Poltekkes Kemenkes Yogyakarta, 2020)
Adolescent groups in society who are at risk of health problems due to dynamic activities, one of which is syncope. Students and the Youth Red Cross (PMR) need to receive socialization on the management of syncope so that morbidity does not occur and can improve health status in schools. The purpose of this community service socialization activity is so that health workers at schools can carry out the first treatment for syncope. The method used was to provide training and health counseling on handling (syncope) to students at SMPN 1 Kayen Kidul in February 2020. Initial results showed as many as 23 students (76.7%) with insufficient knowledge before being given counseling and training on handling (syncope). Posttest results as many as 23 students (76.7%) have less knowledge after being given counseling and training on handling fainting (syncope). Counseling and training activities for handling fainting (syncope) for students at SMPN 1 Kayen Kidul is one of the health activities provided to the school community level to improve health status and prevent morbidity due to fainting (syncope) at school.